An ecotourist friendly fish market at Struisbaai Harbour - Rorich, Nicoll (University of the Free State, 2020)
This dissertation is a proposal for the expansion and improvement of Struisbaai Harbour in the Western Cape. The new additions consist of a promenade element, a swimming platform, a seafront building, a fish market, and a viewing deck on the jetty. The focal point of the proposed new additions will be the fish market element. The role of this proposal is to enhance the livelihoods of the local fishing community allowing for more job opportunities and better infrastructure to execute their daily tasks. The overarching aim of this proposal is to integrate the tourists with the local community. This integration will contribute to a more integrated Struisbaai culture that could benefit all users on the site. To achieve this, it is important to look at ecotourism and to understand how tourism and responsible design can contribute to the betterment of the community. First, the complexities of the research topic are identified and investigated. This is followed by an in-depth exploration of what is needed on the site and why are these elements so important and unique to incorporate into the proposed intervention. Finally, once the complexities and needs of the proposal are identified a deeper exploration is made into creating an appropriate design solution by looking at multiple examples and understanding the context.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2020
Keywords: Ecotourism; Sustainable architecture; Fishing industry - South Africa; Fisher community - South Africa - Struisbaai; Struisbaai (South Africa); Tourism industry - South Africa; Chukkies (small fishing boats); Struisbaai Harbour; Local communities